Pengelolaan Laboratorium Ipa Di Sma Muhammadiyah 1 Sragen - Lestari, Titik, Dr. Sofyan Anif, M.Si, Dr. Suyatmini, M.Si (2017)
Objectives achieved in this study describe about: 1) procurement of equipment and materials science laboratories in SMA Muhammadiyah 1 Sragen; 2) the use of science laboratories in SMA Muhammadiyah 1 Sragen; and 3) maintenance of tools and materials science laboratories in SMA Muhammadiyah 1 Sragen. Type descriptive qualitative research with phenomenological qualitative approach. The technique of collecting data through observation, interview and documentation. This study uses the triangulation of data sources that the principal, deputy head of curriculum and infrastructure, head of the laboratory, laboratory assistants and students. Using descriptive qualitative analysis of data collection, data reduction, data presentation and conclusion or verification. The conclusion of this study, that the science laboratories in SMA Muhammadiyah 1 Sragen is already close to the ideal as per National Standards Laboratory, among others: 1) Procurement of equipment and materials made from planning, procurement and inventory. Procurement within the budget of development funds and BOS, which through three stages, beginning of the year, and the urgent need government assistance and have been using SOP in the planning. 2) The use of the science lab as a place to inculcate scientific attitude of students running optimally, ranging from organizing, scheduling, implementation and administration by the laboratory. Although laboratory serves as a teacher but intertwined coordination and good communication in the implementation of the laboratory. 3) Maintenance of tools and materials is done routinely and periodically, to minimize the damage. Followed by storage and laboratory evaluation to facilitate the checking, durable and facilitate further practical activities.